2013
DOI: 10.1097/ta.0b013e3182984a7d
|View full text |Cite
|
Sign up to set email alerts
|

Does caring for trauma patients lead to psychological stress in surgeons?

Abstract: Symptoms of PTSD as measured by the STSS were reported in two thirds of study participants but did not correlate with time spent for caring for trauma patients. One in five reported symptoms consistent with a PTSD. Lower resilience scores correlated with risk of symptoms and may be used to identify those surgeons most at risk. Efforts to better identify, address, and moderate these psychological consequences of surgical care may improve both the emotional well-being and the vocational performance of surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…A Canadian study of 280 mental health care providers revealed a mean STSS score of 40.9 in the respondents [14], while rescue workers' scores averaged 33.4 [15], Prevalence across symptoms categories is also highly variable. An examination of 133 surgeons of multiple specialties found intrusive thoughts about patients to be the most frequently experienced symptom, with half the sample reporting them at least occasionally [16]. However, the most common symptom category was Arousal, with the surgeons experiencing symptoms of irritability, sleep difficul ties, and hypervigilance.…”
Section: Discussionmentioning
confidence: 94%
“…A Canadian study of 280 mental health care providers revealed a mean STSS score of 40.9 in the respondents [14], while rescue workers' scores averaged 33.4 [15], Prevalence across symptoms categories is also highly variable. An examination of 133 surgeons of multiple specialties found intrusive thoughts about patients to be the most frequently experienced symptom, with half the sample reporting them at least occasionally [16]. However, the most common symptom category was Arousal, with the surgeons experiencing symptoms of irritability, sleep difficul ties, and hypervigilance.…”
Section: Discussionmentioning
confidence: 94%
“…In a mixed sample of heart/lung transplant teams which included physicians (Carey et al, 2019), STS prevalence was 43%. STS prevalence was 16% in Israeli physicians treating terror victims (Weiniger et al, 2006) and in a more civilian context, 22% of surgeons displayed STS (Warren et al, 2013). STS levels in physicians and nurses from the same departments were also compared.…”
Section: Sts In Healthcare Professionsmentioning
confidence: 99%
“…However, patients may be more satisfied with the consultation than the physicians assume, and the authors argue that this may reflect the physicians' own feelings when working with these patients, including their perception that dissatisfaction is the expected consequence of their inability to offer specific solutions to the patient . Moreover, various studies have discussed the affective reactions of clinicians when facing traumatic clinical situations and when caring for patients with complex chronic pain conditions . These affective reactions include the struggle of managing negative emotions expressed within the patient–physician therapeutic relationship.…”
Section: Introductionmentioning
confidence: 99%